Existence and Nonexistence Results for Classes of Singular Elliptic Problem - Peng Zhang; Jia-Feng Liao (Abstract and Applied Analysis)
The singular semilinear elliptic problem -Δu+k(x)u-γ=λup in Ω, u>0 in Ω, u=0 on ∂Ω, is considered, where Ω is a bounded domain with smooth boundary in RN, k∈Clocα(Ω)∩C(Ω¯), and γ,p,λ are three positive constants. Some existence or nonexistence results are obtained for solutions of this problem by the sub-supersolution method.